Cutaneous diphtheria in a patient just returned from Tahiti. (December 2022) - Menier, Lucie; Bourgea, Emilie; Otto, Marie-Pierre; Dutasta, Fabien; Morand, Jean-Jacques; Janvier, Frédéric
Graphical abstract: Image 1